Wear-resistant nickel-matrix composite coatings incorporating hard chromium carbide particles - Isern, Luis; Impey, Sue; Milosevic, Danijela; Clouser, Sidney J.; Endrino, Jose Luis (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
This work evaluates the influence of plating variables on the morphology, composition homogeneity, and abrasive wear resistance of metal matrix composite coatings. A set of Ni/Cr3C2 coatings were brush plated onto steel coupons modifying two key variables: particle size and brush material. Compositional maps of unprecedented detail have been produced and analysed statistically to enhance understanding of composition distribution. The use of Abbott-Firestone curves to analyse surface morphology enabled the evaluation of valley and peak features. The coating differences highlighted by previous analyses have been compared with their behaviour in abrasive environments, simulated using Taber testing. Moreover, coupling Taber testing with partial compositional maps at different wear stages enabled monitoring of coating wear evolution. This methodology has revealed the importance of particle sedimentation during plating, which increased particle incorporation in the composite coating but also increased composition heterogeneity. The smaller 1.7 μm carbides and abrasive brushes produced coatings with more homogeneous morphologies, higher particle content, and increased resistance against abrasive wear, with a 60% reduction in material loss in comparison to the standard nickel coatings.